Burma's gypsies of the sea - Lengaigne, Frederique; Reisinger, Klaus; Breger, Brian (Washington : National Geographic Television & Film, 2003)
A visit to the Burma, focusing on the people, their culture, the transformation of Burma, religious beliefs and rites, societies, etc.
Title from container
Indonesian subtitles
executive producer, David Royleeditor, Steve Olswang ; sound, Frederique Lengaigne
Narrator: Stan Watt
Keywords: Burma -- Description and travel